KORYDON SMITH AND MIGUEL GUITART - Introducing Architectural Theory. Expanding the Disciplinary Debate - Emminger, Andreas (ZARCH, 2025)
KORYDON SMITH AND MIGUEL GUITARTIntroducing Architectural Theory: Expanding the Disciplinary DebateRoutledge, New York/London, 2024, 278 pp. Tapa blanda. 42,39 $Idioma: Inglés ISBN: 9780367335229